FROM THE EDITOR = Redaksioneel - Lategan, Bernard C. (Scriptura, 1986)
Contributions to this issue focus on problems of exegesis, translation and interpretation theory, and reflect the growing interest in matters of this nature. In a situation here the same biblical text can produce widely diverging readings, it is important that the hermeneutical issues raised by such diversity should receive the necessary attention.Certain changes in the editorial set-up of Scriptura (including the announcement of an international advisory board) are being finalised at the moment, and we hope to give our readers more information about this in the next issue.